3 sinx + cos x/ sin x + 2 cos x = 7 /5; ⇒ 5*(3sin x + cos x) = 7*(sin x + 2 cos x); 15 sin x + 5 cos x = 7 sin x + 14 cos x; 8 sin x = 9 cos x; tg x = 9/8;
1)3 sin^2 x - 2 sin x cos x + 1 = 3 sin^2 x - 2 sin x cos x + sin^2 x + cos^2 x = 4 sin^2 x - 2 sin x cos x + cos ^2 x. 2) 2 cos^2 x + sin x cos x + 3 = 2 cos^2 x +sin x cos x + +3sin^2 x + 3cos^2 x = 3sin^2 x + sinx cosx + 5cos ^2 x.
3sin(-x-2π/3)+3sin5x-1,5sin5x-1,5cos5x=-3sin(x+2π/3)+1,5sin5x-1,5cos5x=
-3sinxcos2π/3-3cosxsin2π/3+1,5sin5x-1,5cos5x=1,5sinx-3√3/2cosx+
+1,5sin5x-1,5cosx=1,5(sinx+sin5x)-3√3/2cosx-1,5cos5x=3sin2xcos6x--3√3/2cosx-1,5cos5x